A critical analysis of housing provision, livelihood activities and social reproduction in urban communities in South Africa: the case of Ezamokuhle, Mpumalanga - Nkambule, Sipho Jonathan (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The post-apartheid South African state has formulated, introduced and implemented nationwide policies and programmes pertaining to urban housing in order to address and tackle the challenges of social reproduction in and for poor urban black communities. This however has been undermined for a number of reasons, such as state incapacities and the state's neo-liberal overreliance on the market to remedy past injustices. At the same time households, as critical sites of social reproduction in poor urban black communities and under conditions of extreme vulnerability, engage in a range of productive and non-productive activities often in a desperate bid to construct and maintain a semblance of livelihood sustainability. The thesis seeks to critically understand the relationship between state housing programmes and the diverse livelihood activities of poor urban black households in South Africa in the context of an ongoing systemic crisis of social reproduction which exists in these urban communities. This is pursued with specific reference to eZamokuhle Township in Amersfoort, Mpumalanga Province. The thesis is framed conceptually in terms of the notion of social reproduction. In doing so, it brings together two sets of literature which are often disconnected. On the one hand, there is South African literature which critically analyses the post-apartheid state's housing programmes including the many challenges which exist in this regard. On the other hand, there is literature which considers the urban livelihoods of poor black communities in contemporary South Africa and often from within some kind of livelihoods perspective. The thesis is innovative in bringing these two sets of literature together in terms of the overarching notion of social reproduction and providing, therefore, a more holistic and integrated understanding of the multi-dimensional character of social reproduction. The depth of the crisis of social reproduction in eZamokuhle is explicated and examined in this way but in a manner which articulates the lived experiences and agency of eZamokhule households despite vulnerability constraints and challenges.
Keywords: Uncatalogued